The Professor and the President : Daniel Patrick Moynihan in the Nixon White House - Hess, Stephen (Brookings Institution Press, 2015)
What happens when a conservative president makes a liberal professor from the Ivy League his top urban affairs adviser? The president is Richard Nixon, the professor is Harvard's Daniel Patrick Moynihan. Of all the odd couples in American public life, they are probably the oddest. Add another Ivy League professor to the White House staff when Nixon appoints Columbia's Arthur Burns, a conservative economist, as domestic policy adviser. The year is 1969, and what follows behind closed doors is a passionate debate of conflicting ideologies and personalities.Who won? How? Why? Now nearly a half-ce.